Whose English Counts? Indigenous English in Saskatchewan schools - Sterzuk, Andrea (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2008)
AbstractDrawing on the body of North American literature related to English dialect-speaking Indigenous students schooled in majority group classrooms, this commentary paper explores two aspects of institutional racism at work in Saskatchewan schools: (a) the disproportionate representation of First Nations and Metis students in remedial language and speech programs and (b) the relationship and power imbalance between differences in home and school English varieties and educational attainment.